2009
DOI: 10.1016/s0377-1237(09)80130-5
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Expansion in Cleft Lip and Palate using Quad Helix and Rapid Palatal Expansion Screw

Abstract: Background: Management of patients with cleft lip and palate (CLP) includes orthodontic treatment prior to bone grafting. Palatal expansion is done using slow or rapid palatal expansions (RPE). Controversy still exists regarding choice of expansion appliances used. This study was conducted to find out whether the Quad helix appliance represents a reasonable alternative to using conventional rapid maxillary expansion appliance among cleft lip and palate patients. Methods: Twenty cleft lip and palate patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 14 publications
0
35
1
2
Order By: Relevance
“…Some studies achieved an increase of more than 3mm in the 1 st MWC (24,26) ; while others achieved more than 4mm with the Quad-Helix appliances. (28,29,30) The findings of the present study disagree with Hyunh et al (27) and Wong et al (28) , who stated that both the Hyrax and Quad-Helix appliances showed similar amount of intermolar expansion after SME. A likely explanation is that SME has carried out in young patients at preadolescent, so suture has little interdigitation and opens easily under light forces regardless of expander type.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies achieved an increase of more than 3mm in the 1 st MWC (24,26) ; while others achieved more than 4mm with the Quad-Helix appliances. (28,29,30) The findings of the present study disagree with Hyunh et al (27) and Wong et al (28) , who stated that both the Hyrax and Quad-Helix appliances showed similar amount of intermolar expansion after SME. A likely explanation is that SME has carried out in young patients at preadolescent, so suture has little interdigitation and opens easily under light forces regardless of expander type.…”
Section: Discussioncontrasting
confidence: 99%
“…QH anterior extensions were activated against the premolar and canine palatal surfaces, distally rotating the banded molars. The ability to rotate molars with the QH during maxillary expansion was previously reported by Vasant et al 35 The orthopedic effect of the maxillary expansion in BCLP patients was expressed as a lateral displacement of the posterior segments, leading to an alignment of these segments with the premaxilla. The maxillary expansion is important to prepare the maxilla to receive the secondary bone graft.…”
Section: Discussionmentioning
confidence: 64%
“…Lisson et al, 6 concluded that patients with either unilateral or bilateral cleft palate experience sagittal growth inhibition of the maxilla after primary surgery and maxillary advancement after completion of growth are equally needed in both cleft types. Vasant et al, 7 compared the effectiveness of Quad helix and conventional rapid maxillary expansion appliances and found that Quad helix was as effective as conventional rapid maxillary expansion appliances among cleft patients. Oberoi et al, 8 found that multiple missing maxillary teeth, secondary palate procedures including pharyngeal flaps and inconsistent team care with delayed orthodontic intervention are the factors contributing to maxillary hypoplasia that needs maxillary advancement surgery in individuals with nonsyndromic unilateral cleft lip and palate (UCLP) ( Table 1).…”
Section: Sn 6 To 8 Reported About Maxillary Expansionmentioning
confidence: 99%
“…19,26 In case of a severe maxillary reduction in Dorota et al recommended the use of thick-wire appliances such as expander and combination of a Delaire or Petite type face mask to reduce sagittal displacement of maxilla. 18 Concerning maxillary expansion in cleft children many authors recommended the use of rapid palatal expander (RPE) and slow palatal expander (SPE), 7,17 it has been reported that both slow expander(Quad helix) and RPE were capable to correct posterior crossbites in cleft patients but slow expander such as Quad helix represented more advantages in the ability of correcting molar rotation than rapid expander(Hyrax) but unfortunately both of them were not showed significant results in increasing intercanine and molar width expansion (Table 1). 7 Raj M Vyas et al, 17 suggested the use of a new device, in case cleft patient present maxillary hypoplasia rapid palatal expander using a borne-borne distraction device may be used, this type of expander is capable to increase palate surface area by a mean of 28.9mm 2 inter molar distance up to 8.4mm and intercanine increased by an average of 9.5mm, the main advantage of this expander relapse rate is very slow is between 4% and 7% for cleft patients.…”
Section: Introductionmentioning
confidence: 99%